Examining the association between oncology drug clinical benefit and the time to public reimbursement. (1st December 2021) - Thomson, Sasha; Everest, Louis; Witzke, Noah; Jiao, Tina; Delos Santos, Seanthel; Nguyen, Vivian; Cheung, Matthew C.; Chan, Kelvin K. W.
Abstract: Background: We examined if oncology drug indications with high clinical benefit, as measured by the American Society of Clinical Oncology Value Framework (ASCO‐VF) and European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO‐MCBS), received public reimbursement status faster than those with lower clinical benefit from the time of pan‐Canadian Oncology Drug Review (pCODR) recommendation. Methods: Oncology drug indications submitted to pCODR between July 2011 and October 2018 were examined. Included indications had a regulatory approval date, completed the pCODR review process, received a positive pCODR recommendation, and been funded by at least one province. Trials cited for clinical efficacy were used to determine the clinical benefit (per ASCO‐VF and ESMO‐MCBS) of drug indications. Results: Eighty‐four indications were identified, yielding 65 ASCO‐VF and 50 ESMO‐MCBS scores. The mean ASCO‐VF and ESMO‐MCBS scores were 44.9 (SD = 21.1) and 3.3 (SD = 1.0), respectively. The mean time to provincial reimbursement from pCODR recommendation was 13.2 months (SD = 9.3 months). Higher ASCO‐VF and ESMO‐MCBS scores had low correlation with shorter time to reimbursement, ( ρ = −0.21) and ( ρ = 0.24), respectively. In the multivariable analyses, ASCO‐VF ( p = 0.40) and ESMO‐MCBS ( p = 0.31) scores were not significantly associated with time to reimbursement. Province and year of pCODR recommendation were associated with time to reimbursement in both ASCO and ESMO models. Conclusions: Oncology drug indications with higher clinical benefit do not appear to be reimbursed faster than those with low clinical benefit. This suggests the need to prioritize oncology drug indications based on clinical benefit to ensure quicker access to oncology drugs with the greatest benefits. Abstract : This article examined if oncology drug indications with high clinical benefit, as measured by the American Society of Clinical Oncology Value Framework (ASCO‐VF) and European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO‐MCBS), received public reimbursement status faster than those with lower clinical benefit from the time of pan‐Canadian Oncology Drug Review (pCODR) recommendation. It was found that oncology drug indications with high clinical benefit were not significantly associated with shorter time to public reimbursement. These findings suggest the need to implement a transparent system of prioritization to ensure quicker access to oncology drugs with the greatest benefits.